Damar Kurung Melintas Waktu: Preserving Local Culture in the Age of Digital Society - Ika Anggun Camelia; Djuli Djatiprambudi; Martadi; Fera Ratyaningrum (Institut Seni Indonesia Surakarta, 2026)
Cultural conservation is an essential component in efforts to preserve cultural values because it is closely related to strengthening, preserving the environment, and sustainable learning and education. This research aims to identify a form of conservation as well as a supporting factor for the success of local cultural conservation in the digital society era. The research method used is descriptive qualitative through a case study of the “Damar Kurung Melintas Waktu